Production, Characterization, and Toxicity Test of L-asparaginase from Vibrio alginolyticus Bacterial Symbiont of Green Algae Caulerpa lentillifera - Kasturiasih, Ni Putu; Ahmad, Ahyar; Arfah, Rugaiyah A.; Khairunnur, Siti; Soekamto, Nunuk Hariani; Taba, Paulina; Hala, Yusafir; Karim, Harningsih (Molekul, 2023)
L-asparaginase is an enzyme that can be used as an anticancer therapeutic agent. This study aimed to optimize fermentation time for production, optimization, and to test the toxicity of L-asparaginase from Vibrio alginolyticus (V. alginolyticus) bacterial symbiont of green algae Caulerpa lentillifera (C. lentillifera). The activity of L-asparaginase enzyme assay and the toxicity test were done by using the Nessler method and the Brine Shrimp Lethality Test (BSLT) method respectively. The results show L-asparaginase with 66 hours of fermentation time indicates the highest enzyme activity. L-asparaginase mentioned has an optimum enzyme activity of 17.99 U/mL for 30 minutes of incubation time at 37 °C, and pH 7.5. The BSLT results show LC50 value of 17.83 μg/mL indicating the enzyme is bio-toxic with high-level toxicity, which can continue for cytotoxicity tests on cancer cells.